UPAYA PENINGKATAN EKONOMI WARGA MELALUI PENGOLAHAN PASCA PANEN DAN PEMASARAN SAYURAN HIDROPONIK - Enril Fathurrohman, Yusuf; Prashadi Santosa, Arif; Yusnar Kharismasyah, Alfato (Universitas Djuanda, 2023)
The community empowerment program was carried out in Datar Village, Sumbang Banyumas Regency. This empowerment focuses on marketing and post-harvest processing problems where the solution offered is to provide information related to marketing concepts for hydroponic vegetables, post-harvest assistance, and also vegetable processing training. The target of this empowerment is a group of women farmers and villagers who are active in hydroponic cultivation and who are willing to take part in training related to marketing and post-harvest processing. The method used is in the form of lectures/counseling, mentoring, and direct practice in making processed vegetable products from the residents' vegetable cultivation. These stages have been successfully carried out which have had a positive impact on improving the economic welfare of the community and achieving community food self-sufficiency.